2015
DOI: 10.5271/sjweh.3513
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer among coal miners, ore miners and quarrymen: smoking-adjusted risk estimates from the synergy pooled analysis of case–control studies

Abstract: We estimated increased lung cancer risks for male ore miners, coal miners, and quarrymen in a pooled analysis of case-control studies. Risks remained elevated after adjustment for smoking and working in other at-risk occupations. No clear time trend with work duration was observed. The contribution of individual substances to the lung cancer risk needs to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
(41 reference statements)
2
15
0
1
Order By: Relevance
“…A study on lung cancer incidence among miners found a higher lung cancer risk among men employed in mining, especially ore miners and quarrymen. The association remained significant after controlling for smoking and occupational exposure from working in other at-risk occupations [ 44 ]. To incorporate possible occupational exposure, the analysis was repeated for a subset of the male study population including individual occupation in high-risk industries in 1981.…”
Section: Discussionmentioning
confidence: 99%
“…A study on lung cancer incidence among miners found a higher lung cancer risk among men employed in mining, especially ore miners and quarrymen. The association remained significant after controlling for smoking and occupational exposure from working in other at-risk occupations [ 44 ]. To incorporate possible occupational exposure, the analysis was repeated for a subset of the male study population including individual occupation in high-risk industries in 1981.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is strong evidence linking excess lung cancer risk to employment in occupations including construction6; quarries, sand pits and mining7; transportation8 9; painting10 and welding,11 even after adjusting for smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Some Experts asserted the epidemiology data strongly supported the rat was unique but, as yet, was not conclusive. One Expert cited a recent study on coal dust exposed workers as supporting lung cancer occurrence in coal workers exposed to high dust levels (Taeger et al 2015). Several Experts strongly disagreed with the quality and interpretation of this study, citing several recent studies that found no association between coal dust exposure and lung cancer (Attfield and Kuempel 2008;Miller and MacCalman 2010;Stayner and Graber 2011;Morfeld 2013;Morfeld et al 2015).…”
Section: Is the Rat Lung Cancer Response To Pslts Unique From Other Rmentioning
confidence: 95%
“…A majority of workshop experts (9 of 15) asserted that studies in coal miners do not provide proof for elevated lung cancer risks. However, one expert was of the opinion, based on the study of Taeger et al (2015), that elevated lung cancer risk in coal miners cannot be ruled out. As stated previously, several experts strongly disagreed with the quality and interpretation of the Taeger et al (2015) study and cited several studies in support of their position including: IARC (1997), Attfield and Kuempel (2008), Miller and MacCalman (2010), Stayner and Graber (2011), Morfeld (2013), and Morfeld et al (2015).…”
Section: Is the Rat Lung Cancer Response To Pslts Unique From Other Rmentioning
confidence: 99%